Clinical Insights for Cervical Ripening and Labor Induction Using Prostaglandins - Pierce, Stephanie; Bakker, Ronan; Myers, Dean A.; Edwards, Rodney K. (American Journal of Perinatology Reports, 2018)
Cervical ripening is often the first component of labor induction and is used to facilitate the softening and thinning of the cervix in preparation for labor. Common methods used for cervical ripening include both mechanical (e.g., Foley or Cook catheters) and pharmacologic (e.g., prostaglandins) methods. The choice of method(s) for ripening should take into account the patient's medical and obstetric history, clinical characteristics, and risk of adverse effects if uterine tachysystole were to occur. In this narrative review, we highlight the differences between the prostaglandins dinoprostone and misoprostol with respect to pharmacology and pharmacokinetics, efficacy, and potential safety concerns. Practical guidance on choosing an appropriate prostaglandin agent for cervical ripening and labor induction is provided via the use of clinical vignettes. Considering the advantages and disadvantages of each preparation allows clinicians to individualize treatment, depending on the indications for induction and unique characteristics of each patient.
Keywords: prostaglandins; dinoprostone; misoprostol; cervical ripening; labor induction